Exploring your world : the adventure of geography (Washington, D.C. : The Society, 1989)
A general encyclopedia of physical and human geography containing 334 alphabetically arranged entries and more than 1000 illustrations, including photographs, maps, and charts.
Includes bibliographical references (p. 606-607).
Keywords: Geography -- Dictionaries